A Machine Learning Framework for Automated Interview Feedback and Performance Evaluation (Journal of Informatics Education and Research, 2026)
The Smart Interview Coach is a cutting-edge plat- form designed to enhance interview preparation by providing personalized, actionable feedback on candidates’ performance. Utilizing advanced machine learning, natural language process- ing, and audio analysis techniques, the system transcribes audio responses into text, evaluates vocal features such as pitch, speech rate, loudness, and pauses, and conducts sentiment analysis. It also detects filler words and assesses the quality of language used, including grammar, coherence, and vocabulary. At the conclusion of each session, the system generates a comprehensive feedback report, offering insights into strengths and areas for improvement. By offering detailed, real-time analysis, the Smart Interview Coach helps candidates build confidence, refine their communication skills, and improve their chances of success in interviews, making it a valuable tool for both job seekers and recruiters.